Car Crusher - "Wooderson, Philip" (Oxford University Press: Oxford, 2001)
Neil's mum thinks he is a football thug. Ahmed's lost his Saturday job at the car breakers$1 (Ball because of a photo in the paper$1 (Bbut proving their innocence turns out to be very dangerous.s
Keywords: Mystery fiction